2014
DOI: 10.1002/2014tc003637
|View full text |Cite
|
Sign up to set email alerts
|

Paleo-Pacific subduction-accretion: Evidence from Geochemical and U-Pb zircon dating of the Nadanhada accretionary complex, NE China

Abstract: The Nadanhada Terrane, located along the eastern margin of Eurasia, contains a typical accretionary complex related to paleo-Pacific plate subduction-accretion. The Yuejinshan Complex is the first stage accretion complex that consists of meta-clastic rocks and metamafic-ultramafic rocks, whereas the Raohe Complex forms the main parts of the terrane and consists of limestone, bedded chert, and mafic-ultramafic rocks embedded as olistolith blocks in a weakly sheared matrix of clastic meta-sedimentary rocks. Geoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(150 citation statements)
references
References 58 publications
6
134
0
5
Order By: Relevance
“…Because this has traditionally been related to Pacific-plate subduction, it is commonly excluded from the CAOB. However, recent work has indicated that many events here are coeval with late-stage activity in the CAOB (Zhou et al, 2014), and so their histories are closely aligned.…”
Section: Geological Settingmentioning
confidence: 77%
See 2 more Smart Citations
“…Because this has traditionally been related to Pacific-plate subduction, it is commonly excluded from the CAOB. However, recent work has indicated that many events here are coeval with late-stage activity in the CAOB (Zhou et al, 2014), and so their histories are closely aligned.…”
Section: Geological Settingmentioning
confidence: 77%
“…For the mafic rocks, a gabbro from Guanmen recorded an age of 216 ± 4 Ma and a basalt from Dadai (Fig. 4) an age of 167 ± 1 Ma (Zhou et al, 2014), thus establishing a similar range in ages for the igneous components. Detrital zircons within the clastic sedimentary matrix show a range in age from 2530 to 135 Ma (Zhou et al, 2014), indicating deposition in the Early Cretaceous, but with an Archean component similar to zircon ages reported widely from the North China Craton (e.g.…”
Section: Nadanhada Terranementioning
confidence: 80%
See 1 more Smart Citation
“…1; Table 1) were represented by the accretion of the Nadanhada and Taukha terranes along the Sikhote-Alin belt in north-eastern China and the far eastern part of Russia (Zhou et al, 2014;Kemkin and Taketani, 2008;Malinovsky et al, 2008), as well as the South Kitakami-Kurosegawa block along the Sanbagawa and North Shimanto accretional zones in Shikoku. These Cretaceous accretional events were also represented by the south-eastern margin of Honshu and Hokkaido (Barnes, 2003) and a parallel Kyoke granite belt that was generated in the arc and that extended to the southern margin of South Korea and Sikhote-Alin in Russia (Taira, 2001).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These accretional complexes are assumed to have been continuous along the northeast Asian continental margin, but the Shimanto belt was discontinuous between western Japan and Hokkaido because of the deformation of the island arc. Zhou et al (2014) suggested that the Raohe complex in the Sikhote-Alin belt finally accreted to northeast Asia between 137 and 128 Ma. The Sanbagawa belt was divided into two sub-belts by Isozaki et al (2010b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%